Peran Shopee Affiliate Sebagai Media Komunikasi Pemasaran Digital di Era Generasi - Muchamad Loby Lukman; Sri Andayani (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
In the current era, internet has become part of people's lives, especially generation Z. The development of internet technology also has an impact on the economic cycle, especially the product marketing process, which is now often called digital marketing. Progress of digital marketing in Indonesia is proven by existence of several market places that can be accessed easily via smartphone. One of them is Shopee. Existence of Shopee is also a means of supporting business actors to carry out digital marketing communications. One of the popular digital marketing communication media offered by Shopee is the Shopee Affiliate feature. Type of method used is descriptive research with a qualitative approach. All data in this research was obtained through literature study by analyzing every reading presented by previous researchers and also the results of practical field work carried out for 2 months at Diva Digital Marketing. Based on results of the discussion, it is known that Shopee Affiliate is a feature that many people use to get commissions or additional income by sharing product links. The existence of Shopee Affiliate also provides an increase in sales because of the way it disseminates product information that is interesting and arouses interest, especially among generation Z. Therefore, Shopee Affiliate has a big role as a digital marketing communication medium to increase sales of business products on Shopee.